THE EFFECT OF SNOWBALL THROWING STRATEGY TOWARDS STUDENTS' NARRATIVE READING COMPREHENSION - Ferdiansyah; Gumelar, Rizdki Elang; Novari, Ari Fajria (Al-Shobar Publisher, Yayasan Islam Al-Shobar Rawaurip, 2023)
This research paper aims to determine The Effect of Snow Ball Throwing Strategy Towards Students’ Narrative Reading Comprehension Grade at the Tenth of SMAN 6 Pandeglang. This study uses a quantitative approach with a quasi-experimental design research method, which uses three concepts, namely, pre-test, treatment and post-test. The population was 180 students and the samples of this research was 72 students that consisted of 36 students of experimental class and 36 students of control class. The result of post-test both experimental class and control class, after getting the treatment the result of experimental class is 69.30 and control class is 68.47, it means the result of experimental class is higher than control class. In addition, based on the paired samples t-test with the level significant 5% (a=0.05), it found that the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. Because the significance (2 tailed) result the experimental class was lower than level significance 5% (0.000 < a=0.05). The result reveal that using the strategy of throwing snowballs is very helpful and easy for students to learn, this media can improve students' reading comprehension. Based on the result in this study, that the strategy throwing snowballs is very useful for teachers to improve students' reading comprehension, and easy to learn for students.